Roger J. Steiner, Two centuries of Spanish and English bilingual lexicography, 1590-1800. Mouton, The Hague-Paris, 1970; 130 pp. - Wedel, Alfred R. (El Colegio de México, 1976)
Se reseñó el libro: Two centuries of Spanish and English bilingual lexicography, 1590-1800.